The contents of sexual hormones in cows in the early postpartum period - T. E. Grigorieva; N. S. Sergeeva (Аграрная наука Евро-Северо-Востока)
In connection with the organization of large-scale specialized dairy complexes and high concentration of animals in limited spaces it has been pointed stable tendency to increase in cows’ pathology of childbirth and the postpartum period. In the structure of causes that reduce the reproductive performance of cattle, the profitability of the industry management of dairy cattle breeding, postpartum diseases of cows in the form of subinvolution of the uterus and endomiometrity, leading to reduction in their fertility, milk production and premature culling occupy a special place. Experimental investigations were carried out on the basis of JSC “Vurnary meat” of the Chuvash Republic on cows of black-motley breed with an average milk yield of 5.5 thousand kg per lactation. Test groups of 10 animals each formed on the 4-th day of postnatal period out of clinically healthy cows (first group) and patient cows with postpartum endometritis of acute course (second group). As a result of researches there are revealed differences in the course of the postpartum period and the content of specific sex hormones in clinically healthy and endometritis-diseased cows. For endometritis cows early post-natal period was characterized by a high content of progesterone 31.60 nm/l (in healthy 2.13 nm/l) and low estradiol levels E2 - 22.50 pg/ml (in healthy - 51.30). This was the reason for delayed involution of the uterus, increasing the recovery time of the sexual cycle, development of microbes and inflammation, which led to the weakening of the degenerative-regenerative processes in the endometrium. In cows with endometritis time of lochia allocation increaseв by 5.00 (p < 0.01) days; the duration of involution of the uterus - by 11.90 (p < 0.01) days; the time from birth until fertilization - by 16.8 (p < 0.01) days.